2019
DOI: 10.3389/fped.2019.00308
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Neutrophil to Lymphocyte Ratio and Clinical Outcome in Pediatric Patients After Cardiopulmonary Bypass Surgery: A Retrospective Study

Abstract: Background: The aim of this study was to investigate the prognostic role of the neutrophil to lymphocyte ratio (NLR) in pediatric patients undergoing open-heart surgery with cardiopulmonary bypass (CPB). Methods: A retrospective cohort study of 61 pediatric patients who underwent CPB in the First Affiliated Hospital of Nanjing Medical University from January 2017 to October 2018 was conducted. All perioperative clinical data, including neutrophil count, lymphocyte count, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 21 publications
1
39
1
1
Order By: Relevance
“…ECMO support is reported to increase the NLR values, and patients with high NLR have an increased risk for renal complications and mortality compared to those with a lower ratio ( 28 ). In CPB, higher NLR is associated with longer extubation time and a longer duration of ICU stay, consistent with ECMO ( 75 ). The prognostic capacity of NLR is further demonstrated across various critical illnesses ( 56 , 76 , 77 ).…”
Section: Impact On the Adaptive Immune Leukocytesmentioning
confidence: 69%
“…ECMO support is reported to increase the NLR values, and patients with high NLR have an increased risk for renal complications and mortality compared to those with a lower ratio ( 28 ). In CPB, higher NLR is associated with longer extubation time and a longer duration of ICU stay, consistent with ECMO ( 75 ). The prognostic capacity of NLR is further demonstrated across various critical illnesses ( 56 , 76 , 77 ).…”
Section: Impact On the Adaptive Immune Leukocytesmentioning
confidence: 69%
“…Recent studies perceived that the higher pre-operative NLR in children with CHD was not only associated with a higher risk for low cardiac output in the early post-operative period but also correlated with mortality [ 5 7 ]. Besides, Xu et al found that post-operative NLR in pediatric patients with CHD after CPB was significantly higher than those before operation, which was consistent with increased mechanical ventilation time and intensive care unit (ICU) stay time [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their article describes the association of NLR and C-reactive protein (CRP) with clinical outcomes (length of surgery, extubation time, ICU LOS, hospital LOS), and demonstrated increased NLR to be associated with delayed extubation time and prolonged ICU LOS (P < .05). 11 Two additional studies on biomarkers focused on detection of postoperative blood stream sepsis, which continues to be a major cause of morbidity and mortality in children undergoing cardiac surgery. The first study by Abqari et al evaluated markers of inflammation and infection in 275 infants undergoing cardiac surgery and compared them with those patients with positive blood cultures in the first postoperative week.…”
Section: Predictors Of Outcomes In Congenital Cardiac Surgerymentioning
confidence: 99%